The Politics of Comics: Popular Modernism, Abstraction, and Experimentation. Issue 2 (February 2015) - Worden, Daniel
Abstract Comics and graphic novels are now widely accepted to be legitimate aesthetic and literary texts, suitable for study in all manner of university classrooms and scholarly projects. Comics studies scholarship was often preoccupied with arguing for the aesthetic legitimacy and literary complexity of comics and graphic novels, and now that this debate is more or less over, comics studies scholarship has begun to consider not just why and how we should read comics but what comics might mean. The question of meaning is an inherently political question, as it asks us to think of comics in relation to our social world. This essay traces two ways that comics can be read politically: as part of popular modernism, and as a medium for experimentation with genre, narrative, and visual conventions.